202 Leading integrated child health through COVID-19: responding with local communities, for local communities. (16th November 2020) - Soni, Arpana; Watson, Mando; Rutherford, Phoebe
Abstract : Context: Connecting Care for Children (CC4C) is a leading partnership organisation, that works alongside local providers of child health and with local communities, to support the delivery of integrated child health services. CC4C's model of care puts the General Practioner (GP) at the centre. Joint clinics with GPs and Paediatricians, and multidisciplinary team (MDT) meetings are hosted by primary care centres across central NW London. The Issue: Organisational changes instituted at the start of Covid-19, messaged to CYP and families not to attend primary care centres and Accident and Emergency. The challenge for health professionals was accessing those with health needs and delivering joined-up care without the facility of face-to-face clinics and MDT meetings. Assessment of the Issue Through established community networks, CC4C listened and heard that local primary care teams and communities were in need of child health leadership. Primary care physicians requested paediatric support to manage cases within the new healthcare landscape. Carers, struggling with uncertainty, loss of control and access to services, requested health information from trusted sources. Intervention: Joint clinics and MDTs swiftly moved to virtual platforms. Simple clinical guides to support management of acutely unwell CYP were created and shared through primary care channels. Bundles of information were co-designed and shared with local carers. CC4C co-hosted child health GP webinars and collaborated with local community groups to organise parent/carer webinars. Impact: GPs reported increased confidence with patient management, improved ability to support families to self-manage and continued interprofessional learning. Carers reported reduced anxiety and more appropriate use of healthcare. Understanding local need, designing responsive interventions, reaching out via existing community groups and harnessing peer-to-peer influence has allowed for our success.